Focal points still difficult? Some reflections on German grammar for Slavic native speakers - Kostrova, Olga; Prokop, Izabela (Glottodidactica, 2020)
The aim of this article is to present the project of a contrastive Polish-German and Russian-German grammar, which arose as a result of the cooperation between Samara State University of Social Sciences and Education and Adam Mickiewicz University in Poznan. The idea of a unilateral grammar which is based on the categories of the mother tongue of the learner and is aimed at the foreign language to be learned, is designed as a suitable measure within the framework of error prevention. The grammar contains selected grammatical categories that are significant sources of errors for native Slavic speakers.